FIELD DISPOSITION OF THE MARGINAL STRIP OF THE RIVER DIKE UTILISING WOODEN RAFT AND PILE FOUNDATION ON SOFT CLAY - Suman Manandhar; Daisuke Suetsugu; Hiroyuki Hara; Shigenori Hayashi (Lowland Technology International, 2014)
Full scale field experimentations were incorporated along the downstream of the Chikugo River, Saga, Japan in order to observe the effect of wooden raft and pile foundation on the soft clay. In this study, the wooden raft and pile foundation was utilised for the marginal strip to understand the disposition of vertical settlements and lateral displacements of the ground. Cypress wood was taken into consideration in order for constructing raft and pile. Two different types of wooden raft and pile foundations with same dimensions were installed in the ground. The wooden raft installed with single-sided assemblages of wooden piles was configured as Case I. While, the same raft with both-sided assemblages of wooden piles was configured as Case II. A new embankment was constructed embedded with the existed ones on the river dike. The study was carried out for 136 days span of time from the beginning of the embankment construction. The results showed that both side assemblages of wooden piles were more effective to prevent the lateral displacement, reduce the vertical settlement and local deformation of the dike and the surrounding ground with compared to the single-sided installed piles of the similar foundation structure. The test results confirmed that the river dike supported by the wooden raft and pile foundation can be anticipated as more stable on sand layer of the soft ground within the depth of pile length.